Peranan Guru Kelas Dalam Pelaksanaan Bimbingan Konseling Untuk Penguatan Moral Siswa Kelas V SD N II Giriyoso - Uswatun Khasanah, Siti, Dra. Ratnasari Diah Utami,M.Si., M.Pd (2017)
Research in SD N II Giriyoso aims to describe: 1) The role of classroom teachers in the implementation of guidance and counseling for moral reinforcement of class students. 2) obstacle the role of classroom teachers in the implementation of guidance and counseling for moral reinforcement of class students v 3) effort to the role of classroom teachers in the implementation of guidance and counseling for moral reinforcement of class students v. Qualitative research using case study research design. The subjects of this research are principal, teacher of class V and class V students. Data collecting method using interview, observation and documentation. The results of this study show as follows: 1) Classroom teachers carry out counseling guidance that serves to prevent and improve the moral deviation in students. Aspects of moral reinforcement include: religious teachings, tolerance, discipline, self potential, courtesy and honest. 2) obstacles faced in moral strengthening of the competence of classroom teachers as mentor not qualified, counseling management less organized, moral reinforcement that has not been supported by family and community environment, moral reinforcement has not been fully done by students and moral reinforcement is less supported by teachers. 3) efforts are made to overcome the existing obstacles that is the improvement of classroom teacher competence as a mentor, to improve the management of guidance counseling, environmental in synergy in strengthening students' morale, awareness of students to receive moral reinforcement and giving exemplary moral strengthening by teachers.